Uma proposta de lista de verificação para avaliação de praças - Maciel, Mariana Altoé (2016)
With the population growth of Brazilian cities increasing, it is necessary to establish a greater focus on the needs of people who use the cities. The concern of this research is with the design of the square and its relationship with the user's behavior,